2019
DOI: 10.1111/ssm.12333
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the amount and characteristics of writing prompts in Grade 3 mathematics student books

Abstract: Curriculum guidelines and professional organizations’ recommendations lack details about how often and how much students should write in mathematics and what characteristics should define their writing. This study presents an analytic framework that addresses how often students are prompted in student mathematics books to write, how much they may be encouraged to write, and the characteristics of the writing prompts. Consequently, 2,095 writing prompts in student books across 10 comprehensive Grade 3 resources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Even and Olsher (2014) also stated that teachers presume it is easier to give assignments using textbooks. It is in accordance with Casa et al (2019), which stated that the majority designed their tasks based on the textbook without further adaptations. This finding emphasizes that teachers' beliefs about problem-based tasks are less available in the textbooks they use in class, but it has no clear procedures and contexts.…”
Section: Figure 9 Spldv Task By Nhsupporting
confidence: 75%
“…Even and Olsher (2014) also stated that teachers presume it is easier to give assignments using textbooks. It is in accordance with Casa et al (2019), which stated that the majority designed their tasks based on the textbook without further adaptations. This finding emphasizes that teachers' beliefs about problem-based tasks are less available in the textbooks they use in class, but it has no clear procedures and contexts.…”
Section: Figure 9 Spldv Task By Nhsupporting
confidence: 75%
“…p. 14). If applied, prompting questions should have been accompanied with the required length of writing in phrases such as “in one or two paragraphs, explain how…” write a one‐page report on…,” “write a short essay of not more 200 words on…” With these specific and explicit instructions, learners become guided on the amount of writing required and expected responses (Casa et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For our analysis, we adapted some codes from Casa et al's work and conducted a review of the textbooks and identified other generative writings as codes in the textbooks that presses students to “research about,” “explain how,” “discuss their idea,” “give definition” and to describe the “real‐world example” or “an application of a concept”—which were not captured in the framework developed and validated by Casa et al (2019). Once we reached an agreement on the coding scheme, the codes that requires generative writings were included in the final coding scheme (see Table 2).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations